Hyperoside (quercetin-3-O-β-D-galactopyranoside) protects A2E-laden retinal pigmented epithelium cells against UVA and blue light-induced apoptosis in vitro and in vivo. (January 2018) - Kim, Jun; Jin, Hong Lan; Jang, Dae Sik; Jeong, Kwang Won; Choung, Se-Young
Highlights: Hyperoside protects RPE cells from blue light, UVA and A2E. Hyperoside inhibits apoptosis via inhibiting AP-1 pathway and C3 activation. Hyperoside inhibits retinal degeneration induced by blue light and UVA in mice. Abstract: Age-related macular degeneration is associated with the degeneration of photoreceptors and retinal pigmented epithelial (RPE) cells in the macular. We, previously, demonstrated the protective effect of hyperoside on RPE cell death. In this study, hyperoside inhibited A2E accumulation and UVA and blue light (BL) induced cell death in RPE cells. Hyperoside exhibited inhibitory effects on AP-1 and NF-kB activities, determined by luciferase assay. BL induced complement C3 activation and poly ADP-ribose polymerase (PARP) cleavage were inhibited by hyperoside treatment in A2E laden RPE cells. Furthermore, expression of AhR target genes ( CYP1A1 and CYP1B1 ) were upregulated by hyperoside treatment. Finally, hyperoside prevented UVA and BL-induced photoreceptor degeneration in the Balb-c mice. The outer nuclear layer thickness, counts and retinal layer folds were ameliorated by hyperoside treatment. The results suggest that hyperoside could be a potential application to prevent the onset and development of AMD.